Rheumatic heart disease across the Western Pacific: not just a Pacific Island problem. Issue 2 (5th October 2017) - Abouzeid, Marian; Katzenellenbogen, Judith; Wyber, Rosemary; Watkins, David; Johnson, Timothy David; Carapetis, Jonathan
Abstract : Some of the highest recorded rheumatic heart disease (RHD) prevalence and mortality rates are from the World Health Organization's Western Pacific Region (WPR). RHD burden has been well documented in much of the WPR subregion of Oceania, but less is known about RHD outside the Pacific Islands and Australasia. We aimed to review RHD burden in WPR outside Oceania to identify countries with high RHD burden and those with contemporary data gaps. We searched the peer-reviewed literature for English-language primary studies published between 1980 and April 2017 that reported RHD prevalence or mortality in the 13 WPR countries/areas outside Oceania, and Taiwan. We also searched for official government reports and health indicator documents. Results were synthesised narratively and reported stratified by 2015 Human Development Index (HDI) level. 30 peer-reviewed publications fulfilling inclusion criteria were identified, representing nine countries/areas. RHD prevalence and mortality have fallen in association with economic development, particularly in very high HDI countries. In several countries that have undergone recent economic development, RHD persists particularly among older populations. In poorer WPR countries there is a persistent RHD burden, including in young populations. Some countries had no available data. Although RHD burden has declined in many high-resource settings across the WPR, in several poorer countries, the impact of RHD appears to continue. Elsewhere, insufficient contemporary data make it difficult to gauge the current status of RHD burden and control. Concerted efforts are needed to fill information gaps and implement action to address this avoidable disease.